Professional Social Workers in the Era of Revolution 4.0 (Case Study in Medan ODH Social Rehabilitation Center) - Agussani Agussani; Emilda Sulasmi (Universitas Islam Negeri Sjech M. Djamil Djambek Bukittinggi, 2021)
Abstract This article aims to explain the challenge professional social workers in order to empower the community based on their license. The method used in this study is qualitative method with the study in ODH Social Rehabilitation Center